Effect of climate change and deforestation on vector borne diseases in the North-Eastern Indian State of Mizoram bordering Myanmar - Balasubramani Karuppusamy; Devojit Kumar Sarma; Pachuau Lalmalsawma; Lalfakzuala Pautu; Krishanpal Karmodiya; Praveen Balabaskaran Nina (Elsevier, 2021)
Malaria and dengue are the two major vector-borne diseases in Mizoram. Malaria is endemic in Mizoram, and dengue was first reported only in 2012. The study was designed to study the impact of climate variables, and deforestation on the incidence of dengue and malaria in Mizoram. Temperature, rainfall, and humidity data of Mizoram in the monsoon period (May-September) from 1979 to 2013 were obtained from the National Centers for Environmental Prediction Climate Forecast System Reanalysis. Forest cover data were extracted from the Forests Survey of India Reports and satellite products of Advanced Very High Resolution Radiometer and Moderate Resolution Imaging Spectroradiometer missions. Vector-borne diseases data were obtained from the State Vector Borne Disease Control Program. Non-parametric tests (Mann-Kendall test and Sen's slope method) were used to estimate the long-term trends in the climate and forest cover variables. The Mann-Kendall test indicates that the minimum temperature during the monsoon period is increasing (p<0.001). The Sen's slope estimate shows an average annual 0.02 °C (0.01-0.03 at 95% CI) increase in minimum temperature, and there is an annual ~0.1 °C increase after 2007. There is a 20.45 mm increase in annual monsoon rainfall (5.90-34.37 at 95% CI), and a 0.08% (0.02-0.18 at 95% CI) increase in relative annual humidity. Forest cover data shows that there is an annual average decrease of 162 sq.km (272.81-37.53 at 95% CI, p<0.001) in the dense forest cover. Malaria transmission continues to be stable in Mizoram; compared to 2007, cases have increased in 2019. Over the study period, in the monsoon season, there was an ~0.8 °C rise in the minimum temperature, which could have facilitated the establishment of Aedes aegypti in Mizoram. Furthermore, the increase in rainfall and humidity may have also helped the biology of Ae. aegypti. Deforestation could be an important factor responsible for the consistently high number of malaria cases in Mizoram.